Around the Concept of Urban Landscape - Stadtlandschaft - Grzeszczuk-Brendel, Hanna (Porównania, 2024)
The urban landscape concept refers to the urban environment, integrally combining green areas and buildings. The origins of this way of thinking date back to the turn of the nineteenth and twentieth century, and in the interwar period it became increasingly common among urban planners. This idea gained particular importance during the Third Reich, defining the hierarchy of “organic” spatial planning, which is the main topic of this article. Nowadays, this concept—devoid of its negative connotations—is becoming more and more important in relation to urban transformation and climate challenges.